Rancang Bangun Portal E-Commerce Semarang-Handycraft Berorientasi Obyek - Galih, Sinta Tridian; Mustafid, Mustafid; Sugiharto, Aris (Universitas Diponegoro, 2011)
Number of emerging Small and Medium Enterprises (SMEs) in Indonesia has not been matched with optimal performance. Manyproblems arise such as difficulty in marketing products and limited costs for marketing. This problem can be overcome by utilizingInternet technology to build e-commerce portal. Portal help online marketing with no borders zone, facilitate for searching a consumer,can automate the promotion and business transactions that can help win the competition.In this research, to be built e -commerce portalSemarang-Handycraft. Design of e-commerce portal is using system development methodologies Model Driven Development (MDD)and UML modeling language (Unified Modeling Language) which is a visual language for modeling object -oriented language and byusing the Open Source Content Management Systems that is called Joomla and using e-commerce modules Virtuemart. Produced ecommerce portal that can provide information with better quality and can be accessed at http://semarang-handycraft.cz.cc, which is a newalternative for the production of marketing handicraft products of SMEs in Semarang. For security and convinience of informationretrieval in e-commerce portal is divided into several access rights, ie rights of access to regular visitors, members and administratorsKeywords: E-commerce; Portals; UML; Object-oriented